2011
DOI: 10.2478/v10117-011-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Winter Oilseed-Rape Yield Estimates from Hyperspectral Radiometer Measurements

Abstract: Abstract. Spectral reflectance data can be used for estimation of plant biophysical parameters such as seed yield, related to the use of solar energy. A field experiment was conducted to investigate relationships between canopy reflectance and seed yield of winter oilseed rape sown on four different dates. Ground hyperspectral reflectance measurements were made using a hand-held radiometer and multispectral images were taken with a VIS-NIR camera. The different sowing dates generated a wide range of difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…For both study sites, our results demonstrate that the NDVI-yield relationship weakens as bloom intensifies in agreement with Piekarczyk (2011). The Oregon and North Dakota study sites show the same patterns/trends regardless of growing environment and sensor resolution.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…For both study sites, our results demonstrate that the NDVI-yield relationship weakens as bloom intensifies in agreement with Piekarczyk (2011). The Oregon and North Dakota study sites show the same patterns/trends regardless of growing environment and sensor resolution.…”
Section: Discussionsupporting
confidence: 78%
“…Prior remote sensing research on canola has demonstrated the importance of timing for image acquisition if estimating relationships with grain yield. It has already been established that flowers in a canola canopy are problematic for relating NDVI to yield (Basnyat et al, 2004;Piekarczyk, 2011). An important temporal finding is that the relationship between NDVI and yield declines as flowering increases (Piekarczyk, 2011); however, no spectral solution to this problem has been offered to-date.…”
Section: Canola Yield Modeling Using Remote Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a hand-held radiometer to measure hyperspectral reflectance data and a VIS-NIR camera to capture multispectral images, Piekarczyk et al [29] found the strongest relationship (R 2 = 0.87) between the spectral indices and yields from oilseed crops at early flowering stages on experimental plots in Poland. The authors also found that while the increasing presence of flowers weakened this relationship, especially in the visible range, a strong relationship (R 2 = 0.72) was obtained at full flowering from VIs in the NIR bands.…”
Section: Introductionmentioning
confidence: 99%